2004
DOI: 10.1038/ng1391
|View full text |Cite|
|
Sign up to set email alerts
|

A functional variant of SUMO4, a new IκBα modifier, is associated with type 1 diabetes

Abstract: Previous studies have suggested more than 20 genetic intervals that are associated with susceptibility to type 1 diabetes (T1D), but identification of specific genes has been challenging and largely limited to known candidate genes. Here, we report evidence for an association between T1D and multiple single-nucleotide polymorphisms in 197 kb of genomic DNA in the IDDM5 interval. We cloned a new gene (SUMO4), encoding small ubiquitin-like modifier 4 protein, in the interval. A substitution (M55V) at an evolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
346
3
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 366 publications
(374 citation statements)
references
References 26 publications
9
346
3
5
Order By: Relevance
“…The question remains whether the very same genes are involved in both diseases or whether in the case of genes within the MHC region, the two diseases are due to different genes in linkage disequilibrium. Recently, a number of non-MHC susceptibility genes have been identified in various autoimmune disorders, including interferon regulatory factor 5 (IRF5), protein tyrosine phosphatase nonreceptor-type 22 (PTPN22), small ubiquitin-like modifier 4 (SUMO4) and MHC class II transactivator (MHC2TA) [35][36][37][38]. This has prompted a search for an association in PID patients not only for genes involved in B cell development or immune regulation, but also genes primarily thought to be involved in the development of autoimmunity.…”
Section: Negative Association Studies In Igad/cvidmentioning
confidence: 99%
“…The question remains whether the very same genes are involved in both diseases or whether in the case of genes within the MHC region, the two diseases are due to different genes in linkage disequilibrium. Recently, a number of non-MHC susceptibility genes have been identified in various autoimmune disorders, including interferon regulatory factor 5 (IRF5), protein tyrosine phosphatase nonreceptor-type 22 (PTPN22), small ubiquitin-like modifier 4 (SUMO4) and MHC class II transactivator (MHC2TA) [35][36][37][38]. This has prompted a search for an association in PID patients not only for genes involved in B cell development or immune regulation, but also genes primarily thought to be involved in the development of autoimmunity.…”
Section: Negative Association Studies In Igad/cvidmentioning
confidence: 99%
“…SUMO4 encodes a protein involved in the ubiquitination of IkBa, and a single nucleotide polymorphism (SNP) causing methionine to valine substitution (rs237025, A163G, M55V) results in greater NF-kB transcriptional activity. 4 This polymorphism has been associated with susceptibility to AITD, type 1 diabetes (T1D) and rheumatoid arthritis in Asian populations. 5,6 However, the association of M55V with Graves' disease (GD) and T1D could not be replicated in Caucasian populations, suggesting heterogeneity in the genetic effect of the SUMO4 locus among diverse ethnic groups.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] MAP3K7IP2 (also known as TAB2) encodes a different inhibitor of the NF-kB signaling pathway and a SNP (001Msp) has been shown to be associated with AITD. 4,9 Recently, a functional NFKB1 promoter polymorphism (À94ins/del ATTG) has been identified and associated with the development of ulcerative colitis. 11 In this study, we analyzed the association of this polymorphism with GD.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 SUMO4 is a novel gene located entirely within the 6th intron of the TAB2 gene. IkBa, a negative regulator of NFkB, is a substrate for SUMO4.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] The TAB2/SUMO4 locus maps within the region that has been designated as IDDM5 based on prior linkage studies in ASP families. 18 Two independent studies genotyped overlapping 300 and 320 kb intervals in the IDDM5 region with 18 and 15 SNP markers, respectively. 18,24 Both studies identified markers that displayed strong evidence of association with T1D in either family-based transmission/disequilibrium tests (TDT) or case-control tests.…”
Section: Introductionmentioning
confidence: 99%